Range shifts are part of domestication - Kenneth R Young (Frontiers of Biogeography)
The diversification of species, breeds, and landraces inherent to the domestication of useful taxa is associated with range shifts. As a result, biogeography has many opportunties to interact with new findings about domestication to add an important spatial dimension to research efforts.